NON-STANDARD LAGRANGIANS WITH DIFFERENTIALS OPERATORS - El-nabulsi, R. A.; Rezazadeh, H. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
Nonlinear dynamics from fractional variational approach characterized by non-standard Lagrangians holding singular Weinstein and higher-order extended Euler-Poisson derivative operators are presented in this work. Many results that can enrich the theory of analytical mechanics are obtained and discussed.